Comparison of Clinical and Neuroimaging Characteristics of Congenital and Possible Congenital Cytomegalovirus Infected Infants: A Retrospective Study - Tarakcı, Nuriye; Bulut, Cahide; Çaksen, Hüseyin; Örs, Rahmi (Journal of Pediatric Infectious Diseases, 2019)
Background To evaluate clinical and neurodevelopmental outcomes and neuroimaging results of patients diagnosed with congenital cytomegalovirus (cCMV) infection and those diagnosed with possible congenital CMV (possible cCMV) infection.Methods From January 2014 to January 2016, 24 patients were diagnosed with congenital CMV infection. Clinical and neuroimaging results of these patients were examined from their medical records.Results Of the 24 patients, 6 were diagnosed with cCMV, whereas 18 patients were diagnosed with possible cCMV. Petechia was the most common symptom observed in patients with cCMV infection, whereas microcephaly was more common in patients with possible cCMV. Of the 24 patients, 5 (20.8%) showed normal neuroimaging characteristics. The most commonly encountered abnormal findings in brain magnetic resonance imaging were hypoplasia of corpus callosum (16.7%) and hydrocephalous (16.7%). All of the patients had poor neurodevelopmental outcomes.Conclusions Early diagnosis of asymptomatic cCMV infection is difficult. This study suggests that possible cCMV infections are more prevalent compared with cCMV infections, and delays in diagnosis occur due to not keeping suspicion of CMV infection in early phase. Clinicians should consider long-term neurodevelopmental sequelae of cCMV and possible cCMV infections and remember to screen congenital CMV infection in suspected individuals.
Keywords: congenital CMV; possible congenital CMV; neuroimaging